2013
DOI: 10.1017/s0022029913000502
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alkaline earth metal equilibria on the rheological, melting and textural properties of Cheddar cheese

Abstract: The total calcium content of cheese, along with changes in the equilibrium between soluble and casein (CN)-bound calcium during ripening can have a major impact on its rheological, functional and textural properties; however, little is known about the effect of other alkaline earth metals. NaCl was partially substituted with MgCl2 or SrCl2 (8·7 and 11·4 g/kg curd, respectively) at the salting stage of cheesemaking to study their effects on cheese. Three cheeses were produced: Mg supplemented (+Mg), Sr suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…Ca addition to milk can lead to an increased strength of rennet gels (Sandra et al 2012;Udabage et al 2001;Zoon et al 1988). Cooke and McSweeney (2013) observed that the addition of SrCl 2 at the salting stage of Cheddar cheese manufacture caused significant alterations to its rheological properties, with Sr exhibiting a behavior similar to that previously reported for Ca addition. In the same study, the addition of MgCl 2 at salting had no effect on the rheological properties of cheese.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Ca addition to milk can lead to an increased strength of rennet gels (Sandra et al 2012;Udabage et al 2001;Zoon et al 1988). Cooke and McSweeney (2013) observed that the addition of SrCl 2 at the salting stage of Cheddar cheese manufacture caused significant alterations to its rheological properties, with Sr exhibiting a behavior similar to that previously reported for Ca addition. In the same study, the addition of MgCl 2 at salting had no effect on the rheological properties of cheese.…”
Section: Introductionsupporting
confidence: 77%
“…It is likely that Sr phosphate nanoclusters formed in the SrCl 2 milks. These Sr nanoclusters may have a different stoichiometric ratio of ions compared to conventional Ca-based CCP nanoclusters (Cooke and McSweeney 2013) and may have slightly different properties as a result. In the 10mmol.L −1 CaCl 2 milk gel, the level of CN-bound Ca remained constant between the gelation point and during aging, whereas the CN-bound Mg and Sr decreased in the 10mmol.L −1 MgCl 2 and SrCl 2 milks, respectively, during this time period (Figs.…”
Section: Effect Of Srcl 2 Addition On Mineral Partitionmentioning
confidence: 99%